1999
DOI: 10.1037/0894-4105.13.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between two forms of conceptual priming in Alzheimer's disease.

Abstract: Patients with Alzheimer's disease (AD) and healthy control participants performed 2 conceptual repetition priming tasks, word-associate production and category-exemplar production. Both tasks had identical study-phases of reading target words aloud, had the most common responses as target items, and required production of a single response. Patients with AD showed normal priming on word-associate production but impaired priming on category-exemplar production. This dissociation in AD suggests that conceptual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
5
19
1
1
Order By: Relevance
“…Verification and production tasks have also been used to account for dissociations in performance for different populations, such as nondemented older adults and those with Dementia of the AlzheimerÕs Type Vaidya, Gabrieli, Monti, Tinklenberg, & Yesavage, 1999). Our findings add to this literature that distinguishes between production and verification tests.…”
Section: Discussionsupporting
confidence: 48%
“…Verification and production tasks have also been used to account for dissociations in performance for different populations, such as nondemented older adults and those with Dementia of the AlzheimerÕs Type Vaidya, Gabrieli, Monti, Tinklenberg, & Yesavage, 1999). Our findings add to this literature that distinguishes between production and verification tests.…”
Section: Discussionsupporting
confidence: 48%
“…If so, then it would be consistent with Cermak’s (1997) proposal that the underlying processes which supports implicit memory may be substantially different in controls and patients, and that low-level automatic perceptual repetition fluency can be evident in the absence of other implicit processes (Cermak, 1997; Verfaellie and Treadwell, 1993). However, it is currently unknown how the implicit memory contrast used in the present study may be sensitive to differentiating between the myriad of processes comprising implicit memory (Richardsonklavehn and Bjork, 1988; Vaidya et al, 1999; Voss et al, 2012; Westerman, 2008; Whittlesea, 2002). Hence, future research is needed to determine the extent to which it is sensitive to relative contributions of short term fluency from recent perceptual repetition (Leynes and Zish, 2012; Westerman, 2008) and/or other forms of more permanent influences in implicit memory.…”
Section: 0 Discussionmentioning
confidence: 99%
“…We interpreted the relative sparing of this ERP word repetition effect in amnesia as being secondary to implicit memory processes, likely related to their ability to show semantic 'priming' effects (Graf et al, 1985;Keane et al, 1991;Shimamura, 1986;Shimamura et al, 1987). Therefore, one plausible explanation of this abnormality in AD is that the loss of the N400 repetition effect to incongruous words reflects impairment in semantic priming, as has often been demonstrated in several, but not all, behavioral studies of AD (Albert and Milberg, 1989;Keane et al, 1991;Salmon et al, 1988;Vaidya et al, 1999). It is, however, also possible that the reduced N400 repetition effect in AD is due to impairments in explicit/declarative memory (although there were no significant correlations present with most measures of verbal recall; r's in 0.29-0.44 range with main measures on the CVLT, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Neither paradigm made use of contextual cues or specific semantic associates (e.g. category-target pairs), the formation and storage of which are particularly impaired in AD (Vaidya et al, 1999). Our results are more consistent with the study of Tendolkar et al (1999), in which AD patients showed large reductions in their ERP difference to new-old words (normally present between 400 and 1000 ms in left temporal channels) in an explicit memory (recognition) task with relatively longer time lags (~5 min).…”
Section: Discussionmentioning
confidence: 99%